Speech balloons as transposition of comic dialogue to cinema in Who wants to Jessie? (Kdo Chce Zabít Jessii?, Václav Vorlí?ek, 1966) - Froiz Casal, Luis E. (Fotocinema. Revista científica de cine y fotografía, 2019)
Who Wants to Kill Jessie? (Kdo Chce Zabít Jessii?, Václav Vorlí?ek, 1966) is a film that, from the comedy and from forms closer to the light entertainment cinema, serves as an approach to the communication between the language specificities of comic books and cinema. In the film, the characters that appeared in an adults’ comic book took on corporeal form in the objective diegetic reality, destroying the world and communicating through text balloons. The relationship between the dialogues form from both narrative arts becomes a game that makes us rethink the graphical representation of text and dialogue in cinema, as well as the narrative differences that are shown by the seventh and ninth art due to the differentiation in synchronous and temporal forms. In the same way, the representation of characters incapable of emitting sounds, who communicate only through written text on screen, performs a though about silent movies and its evolution towards sound film, facing two historical moments of cinematographic arts.